Implementasi Pengelolaan Penghidupan Keluarga Sakinah - Beddu, Muhammad Juni; Mas'ari, Ahmad; Yanti, Novi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This study addresses the economic and financial challenges faced by families in Pekanbaru, a major economic and social hub on the island of Sumatra, where many families have low incomes and rely on zakat and infaq assistance to meet their basic needs. High urbanization rates also influence the way families manage their lives. The objective of this research is to identify and analyze the issues families in Pekanbaru face in managing their livelihoods, using a descriptive qualitative approach to comprehensively collect and depict data. The data is analyzed through content analysis to gain a deeper understanding of the challenges. The concept of